Tissue findings in adult fish of Gambusia punctata (Poey 1854) grown under mining influence - Domínguez Odio, Aníbal (2023)
The tissue response of the fish Gambusia punctata (Poey, 1854) grown under natural conditions under chronic heavy metal exposure is reported. Adult individuals of both sexes were captured 10 km downstream of a former open-pit mining area in Santiago de Cuba, Cuba. Branchial deformities with moderate extension were identified in 80% of the investigated individuals. Likewise, 100% presented numerous ferric iron deposits inside the enterocytes.